The Effect of Tax Knowledge, Tax Awareness, Tax Sanctions, and Digital Tax Technology on Individual Taxpayer Compliance in West Jakarta - Septianingsih, Gita; Karnawati, Yosevin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the effect of tax knowledge, tax awareness, tax sanctions, and digital tax technology on individual taxpayer compliance in West Jakarta. The sampling technique used purposive sampling with the following criteria: (1) individual taxpayers domiciled in West Jakarta and (2) those who possess a Taxpayer Identification Number (NPWP). This study employed a quantitative causal approach using primary data collected through questionnaires distributed to 100 individual taxpayers in West Jakarta. The data analysis technique used was multiple linear regression analysis. The results show that, simultaneously, tax knowledge, tax awareness, tax sanctions, and digital tax technology have a positive and significant effect on individual taxpayer compliance. Partially, each independent variable also has a positive and significant effect on taxpayer compliance. Theoretically, this study contributes by reinforcing the application of Compliance Theory in the taxation context, indicating that taxpayer compliance is influenced by knowledge, awareness, tax sanctions, and the utilization of digital technology. Practically, this study provides insights for taxpayers by showing that improving tax understanding, awareness of the importance of taxes, and the use of digital tax systems can facilitate the fulfillment of tax obligations and encourage conscious and sustainable compliance behavior, thereby avoiding tax sanctions.